Fundamental Parameters for Central Stars of 103 Infrared Bow Shock Nebulae - Nikhil Patten; Henry A. Kobulnicky; Matthew S. Povich; Angelica S. Whisnant; Sydney Andrews; Alexandra Boone; Srujan Dandu; Naomi Jones; S. Nick Justice; Dylan Hope; Alexander Larsen; Ryan McCrory; et al. (The Astrophysical Journal)
Stellar bow shock nebulae are arcuate shock fronts formed by the interaction of radiation-driven stellar winds and the relative motion of the ambient interstellar material. Stellar bow shock nebulae provide a promising means to measure wind-driven mass loss, independent of other established methods. In this work, we characterize the stellar sources at the center of bow shock nebulae drawn from all-sky catalogs of 24 μ m–selected nebulae. We obtain new, low-resolution blue optical spectra for 104 stars and measure stellar parameters temperature T _eff , surface gravity ${log}\,g$ , and projected rotational broadening $v\sin i$ . We perform additional photometric analysis to measure stellar radius R _* , luminosity L _* , and visual-band extinction A _V . All but one of our targets are O and early B stars, with temperatures ranging from T = 16.5 to 46.8 kK, gravities from ${log}\,g=$ 2.57 to 4.60, and $v\sin i$ from <100 to 400 km s ^−1 . With the exception of rapid rotator ζ Oph, bow shock stars do not rotate at or near critical velocities. At least 60 of 103 (60%) OB bow shock stars are binaries, consistent with the multiplicity fraction of other OB samples. The sample shows a runaway fraction of 23%, with 19 stars having v _2D ≥ 25 km s ^−1 . Of the 19 runaways, at least 15 (≥79%) are binaries, favoring dynamical ejection over the binary supernova channel for producing runaways. We provide a comprehensive census of stellar parameters for bow shock stars, useful as a foundation for determining the mass-loss rates for OB-type stars—one of the single most critical factors in stellar evolution governing the production of neutron stars and black holes.